Mapping the intellectual structure and emerging trends on nanomaterials in colorectal cancer: a bibliometric analysis from 2003 to 2024 - Lu, Man; Liu, Yi; Zhu, Jin; Shang, Jiarong; Bai, Lu; Jin, Zhichao; Li, Wenting; Hu, Yue; Zheng, Xia; Qian, Jun (Frontiers in Oncology, 2025)
BackgroundColorectal cancer (CRC) is one of thes most prevalent malignant tumors worldwide. Current therapeutic strategies for CRC have limitations, while nanomaterials show significant potential for diagnosing and treating CRC. This study utilizes bibliometric analysis to evaluate the current status and trends in this field.MethodsResearch on nanomaterials in CRC from 2003 to 2024 was retrieved from the Web of Science Core Collection (WOSCC). Tools such as CiteSpace, VOSviewer, RStudio, GraphPad Prism, and Excel were used to analyze trends and hotspots, covering publication trends, countries, institutions, authors, journals, co-citation analysis, and keywords. Visual maps were created to forecast future developments.ResultsThe analysis includes 3,683 publications by 17,261 authors from 3,721 institutions across 100 countries/regions, published in 840 journals. Global publications have steadily increased, particularly since 2018. China leads in publication volume and citations, with six of the top ten research institutions and seven of the ten most cited authors, while the United States excels in citation impact and academic centrality. Both countries currently dominate the field, underscoring the urgent need for enhanced international collaboration. Ramezani M and Abnous K lead in publication volume and H-index, while Siegel RL is highly cited. The International Journal of Nanomedicine has the highest publication volume, while the Journal of Controlled Release is the most cited. In addition to “colorectal cancer” and “nanoparticles,” the most common keyword is “drug delivery.” Emerging research areas such as “metal-organic frameworks (MOFs)” and “green synthesis” are gaining attention as leading hotspots.ConclusionThis study offers an in-depth analysis of the application of nanomaterials in CRC, promoting interdisciplinary collaboration and advancing scientific progress in this field.